2022
DOI: 10.1007/s00330-021-08451-2
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose coronary calcium scoring CT using a dedicated reconstruction filter for kV-independent calcium measurements

Abstract: Low-dose coronary calcium scoring CT using a dedicated reconstruction filter for kVindependent calcium measurements Jubran, Ayman; Mastrodicasa, Domenico; van Praagh,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Furthermore, Jubran et al showed excellent correlation (r = 0.99) between Agatston scores of patients scanned with the standard protocol (120 kVp and standard kernel) and a protocol with a patient-specific tube voltage and a Ca-aware reconstruction technique. 68 The patient-specific protocol was associated with a 21% decrease in median volumetric CT dose index.…”
Section: Reduced Radiation Dose Cac Scoringmentioning
confidence: 97%
“…Furthermore, Jubran et al showed excellent correlation (r = 0.99) between Agatston scores of patients scanned with the standard protocol (120 kVp and standard kernel) and a protocol with a patient-specific tube voltage and a Ca-aware reconstruction technique. 68 The patient-specific protocol was associated with a 21% decrease in median volumetric CT dose index.…”
Section: Reduced Radiation Dose Cac Scoringmentioning
confidence: 97%